Georgia Architectural and Historic Properties Survey of Rural [282] About 4 miles south of Quitman, Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [282] About 4 miles south of Quitman, Valdosta, Ga. December 1980. One story L-shaped house with gabled tin roof. Hipped porch with turned spindle posts and gingerbread. Clapboard siding. Sash windows with 2/2 lights. Interior chimney. Transom over double doors. Set on brick piers. Good condition. Doesn't seem to be a farmhouse. No outbuildings. Set directly off road. Date of Construction: c. 1900. It doesn't look as if there is a farm here, or ever has been. This is a typical vernacular house more common to the urban areas than the rural ones.
Georgia Architectural and Historic Properties Survey of Rural [282] About 4 miles south of Quitman, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.28 MB (1,343,680 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)